(untitled) - Laroy, Clement (New York, 1995)
new addition to an established and popular practical series for teachers, Pronunciation provides a rich resource of imaginative techniques and ideas for teaching pronunciation. Unlike other books on the subject, this book examines why learners fail to achieve good pronunciation and seeks a solution in building their confidence through a holistic approach. This concentrates on rhythm, stress, and articulatory settings first: if these are mastered, individual sounds should follow naturally
Keywords: Eenglish language,English language; pronunciation by foreign speakers.,pronunciation,problems, exercises, etc